Vagal indigestion in cattle - Mazzinghy, Cristiane (Pubvet, 2021)
The vagal indigestion is defined as a non-infectious gastrointestinal pathology of ruminants, characterized by disorders that affect the vagus nerve, and cause motor changes in the pre-stomach of these animals. Vagal indigestion is based on four types: type I is caused by failure of rumen emptying due to cardiac dysfunction, type II is caused by an anterior functional stenosis with hypermotility, type III is caused by posterior functional stenosis, while type IV is identified as late gestation indigestion. The diagnosis requires clinical and laboratory tests, because the clinical signs are non-specific and vary according to where the vagus nerve is involved. The patient diagnosed with vagal indigestion has an unfavorable prognosis. Treatment consists of therapy sessions, administration of bicarbonate, fistulation and/or cannulation of the rumen, and even, because of the multifactorial etiology of vagal indigestion, surgical procedures. It can be concluded, then, that vagal indigestion is a syndrome of great importance in veterinary medicine, which affects and causes disorders in the digestive tract of bovines, and a study on this disease is necessary to ensure and broaden the knowledge of diseases that affect ruminants